Prevalence, Attitude and Predictors of Public Urination amongst Adults attending a Tertiary Health Facility in Uyo, Nigeria - Ekanem AM; Akwaowo CD; Motilewa OO; Udofia EA; Eduwem DU; Akpanekpo E (Ibom Medical Journal, 2025)
Background: Public urination is a widespread sanitation challenge and public health concern with global occurrence and regional variation. Despite its prevalence, empirical data on its determinants and public attitudes remain limited, particularly in low-resource settings. This study aimed to assess the prevalence of public urination, examine public attitudes toward the practice, and identify socio-demographic and behavioural predictors of public urination among adults in Uyo, Nigeria.